Formulasi Biskuit Kelapa Parut Kering dengan Perlakuan Penyangraian dan Tanpa Penyangraian - Yanti Meldasari Lubis; Satriana Satriana; Fahrizal Fahrizal; Eni Darlia (Jurnal Teknologi dan Industri Pertanian Indonesia, 2014)
The study of the formulation of desiccated coconut biscuits by roasting and without roasting was investigated. This research was conducted using randomized block design consisted of two factors and three replications. The first factor is the percentage of the desiccated coconut addition to wheat flour with three levels (25%, 50% and 75%). The second factor is the variation treatment of the desiccated coconut; roasting and without roasting. The result showed that the percentage of desiccated coconut addition to wheat flour has a significant effect on protein content. The treatment of roasting and without roasting has very significant effect on the peroxide number and significant effect on the moisture content, sensory test (aroma and taste). The interaction factor between the percentage of desiccated coconut addition to wheat flour and the treatment of roasting and without roasting has a very significant effect on the fat content and has a significant effect on the sensory test (aroma and taste). The best formulation of the desiccated coconut biscuits based on the sensory test was obtained from the addition of75% of desiccated coconut without roasting.